2017
DOI: 10.1016/j.gdata.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aspirin on the transcriptome of Streptococcus pneumoniae D39

Abstract: Aspirin or acetylsalicylic acid (ASA) is a medicine used to treat pain, fever, and inflammation. Here, we for the very first time reported the genome-wide transcriptional profiling of aspirin-regulated genes in Streptococcus pneumoniae in the presence of 5 mM aspirin in chemically-defined medium (CDM) using microarray analysis. Our results showed that expression of several genes was differentially expressed in the presence of aspirin. These genes were further grouped into COG (Clusters of Orthologous Groups) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…2A ; Data Set S1 in the supplemental material). Consistent with prior studies ( 33 , 42 ), we observed that this subinhibitory level of aspirin led to a largely downregulatory shift in gene expression. Using a cutoff P value of <0.05 and a 2-fold change, we observed 53 genes with significantly lower expression and only 2 genes (both encoding proteins of unknown function) with significantly higher expression when Fn7-1 was grown in 1 mM aspirin.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2A ; Data Set S1 in the supplemental material). Consistent with prior studies ( 33 , 42 ), we observed that this subinhibitory level of aspirin led to a largely downregulatory shift in gene expression. Using a cutoff P value of <0.05 and a 2-fold change, we observed 53 genes with significantly lower expression and only 2 genes (both encoding proteins of unknown function) with significantly higher expression when Fn7-1 was grown in 1 mM aspirin.…”
Section: Resultssupporting
confidence: 92%
“…Aspirin and salicylic acid alter Fn7-1 growth in culture. To probe whether aspirin affects the well-studied F. nucleatum strain Fn7-1, we assayed growth in media supplemented with increasing aspirin concentrations comparable to those used in prior studies (31,33,41) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afzal et al 2017 showed that expression of several S. pneumoniae geneswas differentially expressed in presence of aspirin [25] .…”
Section: According To the Guidelines Of The Clinical Andmentioning
confidence: 99%